2021
DOI: 10.1016/j.celrep.2021.109885
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 activity in Sertoli cells is essential for maintenance of spermatogenesis

Abstract: Sertoli cells are highly polarized testicular supporting cells that simultaneously nurture multiple stages of germ cells during spermatogenesis. Proper localization of polarity protein complexes within Sertoli cells, including those responsible for blood-testis barrier formation, is vital for spermatogenesis. However, the mechanisms and developmental timing that underlie Sertoli cell polarity are poorly understood. We investigate this aspect of testicular function by conditionally deleting Cdc42, encoding a Rh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 68 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…Consistent with these reports, we found that PAFAH1B1 interacts with IQGAP1, and knockdown of Pafah1b1 significantly decreases CDC42 level in murine SCs. Conditional deletion of Cdc42 in Sertoli cells leads to the disrupted Sertoli cell polarity and the perturbed BTB function in adult male mice [60], and inactivation of the CDC42 signaling pathway attenuates the endothelial barrier function in mouse lungs [61]. Our study demonstrates that inhibition of Pafah1b1 results in downregulation of CDC42 and its downstream PAK1, LIMK1, and p-Cofilin.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with these reports, we found that PAFAH1B1 interacts with IQGAP1, and knockdown of Pafah1b1 significantly decreases CDC42 level in murine SCs. Conditional deletion of Cdc42 in Sertoli cells leads to the disrupted Sertoli cell polarity and the perturbed BTB function in adult male mice [60], and inactivation of the CDC42 signaling pathway attenuates the endothelial barrier function in mouse lungs [61]. Our study demonstrates that inhibition of Pafah1b1 results in downregulation of CDC42 and its downstream PAK1, LIMK1, and p-Cofilin.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with these reports, we found that PAFAH1B1 interacts with IQGAP1, and knockdown of Pafah1b1 signi cantly decreases CDC42 level in murine SCs. Conditional deletion of Cdc42 in Sertoli cells leads to the disrupted Sertoli cell polarity and the perturbed BTB function in adult male mice [59], and inactivation of the CDC42 signaling pathway attenuates the endothelial barrier function in mouse lungs [60]. Our study demonstrates that inhibition of Pafah1b1 results in downregulation of CDC42 and its downstream PAK1, LIMK1, and p-Co lin.…”
Section: Discussionmentioning
confidence: 70%
“…Although Sertoli cell polarity is critical for effective spermatogenesis, it is unclear when and how these cells become polarized [ 36 ]. Rho GTPase signaling has been linked to cell polarity and other cellular processes (e.g., cell cycle, cell migration, cytoskeletal structure) in a variety of biological situations [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%